Copyright Protection for Artificial Intelligence-Generated Works: An Analysis of Indonesian Positive Law, Islamic Law, and a Comparative Study with China - Farhan Ardhi Nugroho; Inge Dwisvimiar; Sariyah (JURNAL ILMU SYARIAH, 2026)
The rapid advancement of Artificial Intelligence (AI) has fundamentally transformed the process of creating copyrighted works, giving rise to complex legal issues concerning authorship, originality, and copyright ownership. Indonesian copyright law continues to adopt a human-centered authorship approach but has yet to establish clear legal standards for determining copyright protection for AI-generated works. This study aims to analyze the regulation of AI-generated works under the copyright systems of Indonesia and China and to formulate a reconstructed copyright protection model suitable for implementation in Indonesia. Employing normative legal research with statutory, conceptual, and comparative approaches, this study examines Law Number 28 of 2014 concerning Copyright, the Copyright Law of the People's Republic of China (Amendment 2020), and the Beijing Internet Court decision in LI v. LIU (2023). The findings reveal that Indonesia lacks objective legal parameters for assessing human creative contribution in AI-assisted creative processes, whereas China has adopted a more adaptive approach by recognizing copyright protection based on identifiable human intellectual contribution. From the perspective of Islamic law, AI is regarded as a technological instrument (wasīlah) rather than an independent legal subject, while intellectual property rights remain vested in human beings under the concepts of ḥaqq al-ibtikār and huqūq māliyyah, consistent with the objectives of Maqāṣid al-Sharī'ah. Accordingly, this study proposes the Human Creative Contribution (HCC) model as the principal basis for attributing copyright ownership to AI-generated works, thereby strengthening legal certainty while preserving the human-centered philosophy of copyright.